2014
DOI: 10.1038/ki.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide potently prevents ischemia-induced high-mobility group box 1 translocation and release and protects against lethal renal ischemia–reperfusion injury

Abstract: High-mobility group box 1 (HMGB1) is a chromatin-binding nuclear molecule that has potent proinflammatory effects once released by damaged cells. In some disease models, carbon monoxide (CO) exhibits anti-inflammatory and protective properties. Here, we investigated whether the protective effect of CO on renal ischemia-reperfusion injury is associated with the inhibition of HMGB1 translocation and release. A renal ischemia-reperfusion injury model was established with a 100% mortality rate in untreated mice. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 33 publications
2
39
0
1
Order By: Relevance
“…Based on the present and previous findings, the mechanism of CYP protection by the CO-RBC in the later phase after hemorrhagic shock and resuscitation appears to involve the prevention of inflammatory cytokines as a result of the suppression of both HMGB-1 release from parenchymal cells and TLR-4 expression on Kupffer cells by CO derived from CO-RBC. This proposed mechanism is supported by previous studies which showed that CO has the potential to attenuate HMGB-1 release and TLR-4 activation under other pathological conditions [25][26][27].…”
Section: Discussionsupporting
confidence: 78%
“…Based on the present and previous findings, the mechanism of CYP protection by the CO-RBC in the later phase after hemorrhagic shock and resuscitation appears to involve the prevention of inflammatory cytokines as a result of the suppression of both HMGB-1 release from parenchymal cells and TLR-4 expression on Kupffer cells by CO derived from CO-RBC. This proposed mechanism is supported by previous studies which showed that CO has the potential to attenuate HMGB-1 release and TLR-4 activation under other pathological conditions [25][26][27].…”
Section: Discussionsupporting
confidence: 78%
“…17 Similar protective results can be achieved after storage of grafts in a UW solution saturated with CO. 18,19 Sener et al 20 demonstrated that carbon monoxide releasing molecules (CORM) supplementation in UW solution has a significant impact on decreasing cellular and graft injury, and improving rat kidney graft survival through its anti-apoptotic effects. Recently, Ruan Y et al 21 reported the protective effect of CO from CORM on renal ischemia-reperfusion injury is associated with the inhibition of high-mobility group box 1 (HMGB1) translocation and release. In addition to its antiinflammatory and anti-apoptotic effects, CO reduced graft immunogenicity and inhibited chronic allograft nephropathy in a rat kidney transplantation model.…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase-1 and the heme metabolite CO have been shown to inhibit TLR4 signaling to reduce cytokine-driven inflammatory outcomes and protect cells against oxidative stress (Liu et al, 2002; Otterbein et al, 2005; Nakahira et al, 2006; Tsiftsoglou et al, 2006; Lin et al, 2009; Wang et al, 2009; Ruan et al, 2014; Xue and Habtezion, 2014). In addition to TLR4, CO also inhibits the activation of TLR2, TLR5, and TLR9 (Nakahira et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is thought to contribute to cytoprotection and proliferation through the catabolism of heme, a pro-oxidant molecule that is cytotoxic in excess, into metabolites with anti-oxidant, pro-angiogenic, anti-apoptotic, and anti-inflammatory activities (Ryter and Tyrrell, 2000; Ryter et al, 2006; Ryter and Choi, 2009). Of particular relevance to the current study, the endogenous gasotransmitter CO participates in intracellular signaling pathways that culminate in anti-inflammatory, anti-coagulative and pro-survival outcomes (Liu et al, 2002; Pae et al, 2004; Otterbein et al, 2005; Nakahira et al, 2006; Ryter and Choi, 2009; Ruan et al, 2014; Yang et al, 2014; Xue and Habtezion, 2014; Riquelme et al, 2015). The discovery of compounds categorized as “carbon monoxide releasing molecules” (CORM) has allowed for further mechanistic insight into the role of CO in biological systems (Ryter and Choi, 2015).…”
Section: Introductionmentioning
confidence: 98%